Aspects affecting the choice for scientific journal publishing - Figueiredo, Livia Mara Alves; Palma, Ana Luiza do Rosário; Araujo, Cássia Fernandes; Pedroso, Juliana de Fátima; Jardini, Maria Aparecida Neves; Rode, Sigmar de Mello (Brazilian Dental Science, 2016)
Objective: This study aimed to evaluate the social and academic aspects and factors related to scientific journal that influence and motivate the authors to choose the journal to publish their academic work. Material and Methods: The study was conducted with professors and graduate students of the Institute of Science and Technology of Sao Jose dos Campos, UNESP. Participants responded to an online questionnaire, sent via email, and the data were tabulated and analyzed. Result: The Thomson Reuters impact factor, followed by Qualis CAPES Index were considered of greater importance at the moment of choosing the journal for 56% of respondents. All respondents considered peer review relevant and 89% pointed out double-blind review as the most important aspect. Indexing and the journal’s quality were considered the most significant factors by most respondents. 98% of respondents have knowledge on both open access journals and Digital Object Identifier (DOI). Conclusion: The assessed academic community demonstrated good knowledge on the factors inherent to the publication of scientific papers. Impact factor, indexing, and journal’s quality influenced on scientific journal publishing. Keywords: Impact factor; Magazine article; Periodicals.